2022
DOI: 10.3390/ijms232415623
|View full text |Cite
|
Sign up to set email alerts
|

Retinol-Loaded Poly(vinyl alcohol)-Based Hydrogels as Suitable Biomaterials with Antimicrobial Properties for the Proliferation of Mesenchymal Stem Cells

Abstract: Polyvinyl alcohol (PVA) hydrogels are well-known biomimetic 3D systems for mammalian cell cultures to mimic native tissues. Recently, several biomolecules were intended for use in PVA hydrogels to improve their biological properties. However, retinol, an important biomolecule, has not been combined with a PVA hydrogel for culturing bone marrow mesenchymal stem (BMMS) cells. Thus, for the first time, the effect of retinol on the physicochemical, antimicrobial, and cell proliferative properties of a PVA hydrogel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 93 publications
3
9
0
Order By: Relevance
“…Interestingly, both hydrogels favored the adsorption of protein, and the protein-binding ability was accelerated by AgNPs. Similar to the present study, the protein adsorption of PVA hydrogel was reported to be fabricated with hydroxyapatite-chitosan [54], alginate/dextran [55], 1-Vinyl-3-butylimidazolium bromide and acrylamide [56,57], and retinol [15]. In the present study, the protein adsorption of PVA hydrogel depends on the surface energy, surface hydrophobicity chemical groups, and electrostatic interaction between the proteins and the hydrogel surface [58][59][60].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, both hydrogels favored the adsorption of protein, and the protein-binding ability was accelerated by AgNPs. Similar to the present study, the protein adsorption of PVA hydrogel was reported to be fabricated with hydroxyapatite-chitosan [54], alginate/dextran [55], 1-Vinyl-3-butylimidazolium bromide and acrylamide [56,57], and retinol [15]. In the present study, the protein adsorption of PVA hydrogel depends on the surface energy, surface hydrophobicity chemical groups, and electrostatic interaction between the proteins and the hydrogel surface [58][59][60].…”
Section: Discussionsupporting
confidence: 81%
“…Mechanically stronger and tough hydrogels were fabricated to compensate for the load-bearing ability of cartilage replacement, artificial muscles, artificial organs, and contact lenses [ 7 ]. Several polymers, such as collagen [ 8 , 9 ], chitosan [ 10 , 11 , 12 ], alginate [ 13 , 14 ], poly(Vinyl Alcohol) (PVA) [ 15 ], polyLactic Acid (PLA) [ 16 ], silk fibroin [ 17 ], and cellulose [ 18 ] has been widely used in hydrogel fabrication for regenerative tissue purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical strength of single PVA hydrogel is still not up to the expected effect in some applications [ 33 , 34 ], so taking PVA as the first network and introducing the second network material to prepare double network hydrogel has become a research hotspot. Once tannic acid was introduced into PVA hydrogel and prepared high-strength hydrogel with dimethyl sulfoxide and water as solvents.…”
Section: Mechanical Properties Of Double Network Hydrogelsmentioning
confidence: 99%
“…Their findings highlighted that Mg 2+ released from the hydrogels bolstered the proliferation of BMSCs, whereas curcumin mitigated the damage to BMSCs from H 2 O 2 exposure and reduced apoptotic cells and nuclear condensation. Elango et al [ 176 ] created a PVA retinol hydrogel and discovered that the cell proliferation effect of the PVA hydrogel was significantly enhanced by incorporating 0.1 to 0.5 wt% of retinol. They also found that retinol promotes the differentiation of MSCs into neural cells.…”
Section: Interaction Between Scaffolds and Mscsmentioning
confidence: 99%